Emotional Educational Card Games in Cultivating Moral Values in Learning the Qur'an and Hadith - Uswatun Hasanah; Agus Salam; Irwan (JIE (Journal of Islamic Education), 2026)
This study aims to analyze the implementation of emotional card educational games in Islamic Religious Education (IRE), particularly in the Al-Qur'an Hadith subject, to foster moral values and anti-bullying attitudes among elementary school students. This research also seeks to examine the role of emotion card media in helping students recognize, understand, and manage their emotions positively. This study employed a descriptive qualitative approach using field research conducted at MIN 1 Bima. Data were collected through participatory observation, semi-structured interviews, and documentation with IRE teachers, students, and the madrasah head. Data analysis followed Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The data's validity was ensured through triangulation and member checking. The findings indicate that the use of emotion cards improves students’ ability to recognize and manage emotions, enhances empathy toward peers, and reduces bullying behavior in the classroom. The learning process also becomes more interactive, communicative, and enjoyable, leading to greater student engagement. Students appear more active in discussions and collaborative activities, and they respect their peers’ opinions during learning. Furthermore, integrating emotional aspects with Islamic moral values has proven effective in fostering positive social behavior. This study is limited to a single research site and does not quantitatively measure behavioral changes among students. This study offers an innovative approach by integrating emotion-based educational games into IRE learning to strengthen anti-bullying character education among elementary school students.